Guidance And Counseling Services For Reducing Sexual Cases: Systematic Literature Review - Trilia, Trilia; Nambiar, Nisha; Said, Faridah Mohd (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The school environment is no longer a safe and comfortable place for studying because of cases of sexual that also occur in the school environment. In line with these facts, this study aims to find out and identify the extent to which Guidance and Counseling is dealing with this problem. In the process of writing this literature review, the study material used by the author included several journal references from Google Scholar with search results totaling 319 journals with keywords such as guidance and counseling, school environment systematic, sexual, which had been published in the 2019-2023 period. So, in writing this literature review, the author determined 6 national journals that were appropriate to the topic to be researched. The results of the research obtained from 6 journals studied indicate that there are still many problems related to sexual in the school environment and guidance and counseling services in schools have attempted to overcome and prevent cases of sexual with the curative and preventive services provided.